PRODUCTS AND PRICE POLICY ON CONSUMER DECISIONS TO STAY AT FAVE HOTEL BANDUNG - Pebi Kurniawan; Ali Jufri (Universitas Padjadjaran, 2023)
Tourism plays an important role in the Indonesian economy. It provides a country’s foreign exchange, as well as financial support for building the economy. Additionally, tourism encourages business growth and employment by providing labor needs. The increased number of visitors to Indonesia has spurred significant growth in the country’s tourism industry. This can be seen from the increase of hotels, restaurants, transportation and other services that focus on tourism. Additionally, this can be seen from the increasing number of visitors in Indonesia. This research looks at how Product and Price Policy influences customers’ choices. It does this by gathering data using a SEM-PLS approach and processing 150 respondents from the Fave Hotel Bandung. The study finds that customers’ choices in favor of a particular hotel or the hotel’s price policy directly influence their decisions.